PENGARUH DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT SRIKANDI DIAMOND MOTORS MITSUBISHI ALAM SUTERA - Salsabila, Husvira; Suhartono, Irwan (Journal of Research and Publication Innovation, 2024)
This research aims to find out how work discipline and job satisfaction influence employee performance at PT Srikandi Diamond Motors Mitsubishi Alam Sutera. This research method uses quantitative research methods with a population and sample of 94 employees. The sampling technique used was a slovin sample. The data collection method used was a questionnaire. This research obtained partial results that work discipline has a positive and significant effect on employee performance. Based on the results of the first hypothesis test obtained from the tcount value of the hypothesis test, the value tcount > ttable (9.349 > 1.986) and the results of the simple regression test Y = 15.966 + 0.795 0.05). Thus, H0 is rejected and H1 is accepted, this shows that partially the job satisfaction variable has a significant influence on employee performance at PT. Srikandi Diamond Motors Mitsubishi Alam Sutera. Based on the results of the second hypothesis test obtained from the value tcount > ttable or (10.005 > 1.986) and the results of the simple regression test Y = 12.406 + 0.490 X2. This can also be strengthened with a sig value < 0.05 or (0.000 < 0.05). Thus H0 is rejected and H2 is accepted. This shows that partially the job satisfaction variable has a significant influence on employee performance at PT. Srikandi Diamond Motors Mitsubishi Alam Sutera. Based on the results of hypothesis testing, the value Fcount > Ftable or (73.590 > 2.705) and the results of multiple linear (Y) = 5.336 + 0.353 (X1) + 0.317 (X2) were obtained. Thus, H0 is rejected and H3 is accepted, this shows that simultaneously the variables of work discipline and job satisfaction have an influence on employee performance at PT. Srikandi Diamond Motors Mitsubishi Alam Sutera.